2003
DOI: 10.1093/pcp/pcg068
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Wx Transgene into Rice wx Mutants Leads to Both High- and Low-Amylose Rice

Abstract: ;The Waxy (Wx) gene encodes a granule-bound starch synthase (GBSS) that plays a key role in the amylose synthesis of rice and other plant species. Two functional Wx alleles of rice exist: Wx a , which produces a large amount of amylose, and Wx b , which produces a smaller amount of amylose because of the mutation at the 5¢ splice site of intron 1. Wx b is largely distributed in Japonica cultivars, and high amylose cultivars do not exist in Japonica cultivars. We introduced the cloned Wx a cDNA into null-mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 19 publications
1
52
1
Order By: Relevance
“…For example, the elevated level of GBSSI caused by the introduction of Waxy a into a japonica waxy mutant leads to amylose increase (approximately 25%), in contrast with that of the japonica cv Waxy b (approximately 20%; Itoh et al, 2003). However, when further overexpressing GBSSI in normal cereal crops that usually contain approximately 25% to 30% amylose content, no or little amylose promotion is detected (Flipse et al, 1996;Itoh et al, 2003;Sestili et al, 2012), which means that the Waxy dosage effect is restricted within a range and that GBSSI is not always the key factor to promote amylose content. Flipse et al (1996) suggested that, except for GBSSI, the amylose content of starch potentially correlates with the availability of ADP-Glc and the limited physical space available within the matrix of amylopectin.…”
Section: Regional Distribution Of Three Sbe Isoforms In Developing Enmentioning
confidence: 99%
“…For example, the elevated level of GBSSI caused by the introduction of Waxy a into a japonica waxy mutant leads to amylose increase (approximately 25%), in contrast with that of the japonica cv Waxy b (approximately 20%; Itoh et al, 2003). However, when further overexpressing GBSSI in normal cereal crops that usually contain approximately 25% to 30% amylose content, no or little amylose promotion is detected (Flipse et al, 1996;Itoh et al, 2003;Sestili et al, 2012), which means that the Waxy dosage effect is restricted within a range and that GBSSI is not always the key factor to promote amylose content. Flipse et al (1996) suggested that, except for GBSSI, the amylose content of starch potentially correlates with the availability of ADP-Glc and the limited physical space available within the matrix of amylopectin.…”
Section: Regional Distribution Of Three Sbe Isoforms In Developing Enmentioning
confidence: 99%
“…Previous studies have focused on genes directly involved in the biosynthesis/metabolism of starch, protein and fat [66][67][68][69][70][71][72][73]; our analysis suggests that many other genes may also be involved in seed quality control. Analysis of the underlying complex regulatory network should broaden our understanding of the relevant regulatory mechanisms.…”
Section: Genes Associated With Seed Quality Control Are Involved In Dmentioning
confidence: 80%
“…The alteration of starch quantity and quality can be achieved through the overexpression of some enzymes involved in starch synthesis [60], by mutations or RNAi technology, such as the inhibition of potato SSII, SSIII and GBSS [61], or the decrease in the expression of wheat BEIIa and BEIIb [62,63]. In this way, by affecting the catalytic activity of enzymes involved in the synthesis of amylose or amylopectin, it could be possible to obtain starches for different purposes.…”
Section: Altering the Composition And Amount Of Starch By Biotechnolomentioning
confidence: 99%
“…Other strategy to obtain high amylose starches was carried out by Itoh et al [60]. The Waxy (Wx) gene encodes a granule-bound starch synthase (GBSS) that plays a key role in the amylose synthesis of rice and other plant species.…”
Section: Linesmentioning
confidence: 99%